SEMI-AUTOMATIC SHREDDED BEEF MACHINE - Ryan Effendi; Arif Saputra; Teguh Budi Riono; Irfan Burhanudin Wibowo; Bangkit Krisna Surya Handaru; Agung Prijo Budijono (Journal of International Conference Proceedings (JICP), 2018)
The Purpose The purpose of this study is to provide solutions to existing problems in SMEs Abon Beef Surabaya area in the production process that the process is still using the manual and tools used are still relatively simple. Method The method used is by utilizing Gear Box technology as the mechanism of power distributor from Electric Motors to the meat counter. In this tool also equipped with Electric Motor so that shredded beef process can run automatically. Results The expected result is to increase 1.5 times the productivity of the Abon Beef Cow's SMEs due to its faster and more efficient enumeration process so that it initially produces 40 Kg / day can produce up to 60 Kg / day. The Finding The findings of this research is the use of Gear Box technology and Electric Motor to help improve enumeration ability so that the productivity of SMEsAbon Beef also increases. Keywords: Abon, Cattle Beef Machine, SMEs, Shredded Beef